Large area chemical vapor deposition of monolayer transition metal dichalcogenides and their temperature dependent Raman spectroscopy studies - Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; Late, Dattatray J. (Nanoscale, 2016)
We investigate the growth mechanism and temperature dependent Raman spectroscopy of chemical vapor deposited large area monolayer of MoS2, MoSe2, WS2 and WSe2 nanosheets up to 70 mu m in lateral size. Further, our temperature dependent Raman spectroscopy investigation shows that softening of Raman modes as temperature increases from 80 K to 593 K is due to the negative temperature coefficient and anharmonicity. The temperature dependent softening modes of chemical vapor deposited mono-layers of all TMDCs were explained on the basis of a double resonance phonon process which is more active in an atomically thin sample. This process can also be fundamentally pertinent in other emerging two-dimensional layered and heterostructured materials.